Association between domain-specific physical activity and diabetes in Korean adults - Eun-Byeol Lee (Nature Portfolio, 2021)
Abstract This study aimed to investigate the association between domain-specific physical activity (PA) and diabetes in Korean adults. We analyzed 26,653 men and women (aged > 18 years) from the Korea National Health and Nutrition Examination Survey (2014–2018). PA was measured using a validated Global PA Questionnaire. Multivariable logistic regression was used to estimate odds ratios (ORs) and 95% confidence intervals (CIs) after adjustment for various confounders. Transport PA accounted for the majority of total PA (46%, men; 58%, women), followed by leisure-time PA (30%; 22%) and work PA (24%; 20%). In men, ORs (95% CI) of diabetes comparing ≥ 600 metabolic task of equivalent (MET)-min/week vs. no activity were 0.82 (0.71–0.95) for leisure-time PA, 0.85 (0.75–0.96) for transport PA, and 0.88 (0.78–0.99) for leisure-time + transport PA. In women, ORs (95% CI) of diabetes comparing the same groups were 0.73 (0.60–0.89) for leisure-time PA, 0.97 (0.85–1.10) for transport PA, and 0.88 (0.78–1.00) for leisure-time + transport PA. However, work PA showed no association with diabetes. In conclusion, leisure-time PA was inversely associated with diabetes in both men and women, while transport PA was inversely associated only in men. But work PA was not associated with diabetes in Korean adults.